Changes in Ownership and Ulayat Land Use in Lumban Rau Timur Village, Toba Samosir - Hidayat Hidayat; Lukitaningsih Lukitaningsih (Diponegoro University, 2021)
This study explores the historical background of the establishment and the uses of customary land in Lumban Rau Timur Village. It analyses the process and mechanism of transferring customary rights as well as factors that influence the role of the state and the market in determining the direction and change of the customary land of the Toba Batak people in Samosir Regency. Sources were collected by structured interviews, observation, and literature study. Methods and data analysis uses a descriptive qualitative research approach with a socio-historical approach. The historical background of the formation of ulayat in Lumban Rao Timur Village comes from land clearing and comes from golat land (land grabbing due to land conflicts). Communal land includes areas where ceremonies, graves, rice fields, livestock grazing areas, cultivated forests, expansion areas or settlement expansion, waters and forest areas, wild plants are managed and used together. Ethnics are inhabited by residents who have genealogical and territorial ties. According to tradition, the land should not be transferred to other parties, but over time, there has been a transformation of land ownership to other parties, both local residents who lived in and outside the village, which is intended for agriculture and non-agriculture. The transformation of ulayat land ownership is caused by socio-cultural shifts, demographic pressures, openness information and communication as well as the state penetration via government regulations on natural resources under the development programs in the areas of Lake Toba.